2018
DOI: 10.1007/s00216-018-0852-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends and analytical challenges in plant bioactive peptide separation, identification and validation

Abstract: Interest in research into bioactive peptides (BPs) is growing because of their health-promoting ability. Several bioactivities have been ascribed to peptides, including antioxidant, antihypertensive and antimicrobial properties. As they can be produced from precursor proteins, the investigation of BPs in foods is becoming increasingly popular. For the same reason, production of BPs from by-products has also emerged as a possible means of reducing waste and recovering value-added compounds suitable for function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 134 publications
1
92
0
1
Order By: Relevance
“…Following the method of Piovesana et al [31], the theoretical ACE-inhibitory activity and antihypertensive (AHT) ability of the peptides obtained by LC-MS/MS analysis were screened using the AHTPDB databases (http://crdd.osdd.net/raghava/ahtpdb/) and BIOPEP (http://www.uwm.edu.pl/ biochemia/index.php/en/biopep). The potential ACE-inhibitory peptides were chose based on the B value (the potential biological activity calculated using the activity of the sequence motif published in BIOPEP database) and average local confidence (ALC; if it was above 85%).…”
Section: In Silico Screening Of Peptides and Chemical Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Following the method of Piovesana et al [31], the theoretical ACE-inhibitory activity and antihypertensive (AHT) ability of the peptides obtained by LC-MS/MS analysis were screened using the AHTPDB databases (http://crdd.osdd.net/raghava/ahtpdb/) and BIOPEP (http://www.uwm.edu.pl/ biochemia/index.php/en/biopep). The potential ACE-inhibitory peptides were chose based on the B value (the potential biological activity calculated using the activity of the sequence motif published in BIOPEP database) and average local confidence (ALC; if it was above 85%).…”
Section: In Silico Screening Of Peptides and Chemical Synthesismentioning
confidence: 99%
“…The results in Table 2 demonstrate that there were 17 peptides identified in fraction D11 by LC-MS/MS analysis. The potential antihypertensive peptides were screened based on the theoretical ACE-inhibitory activity (B) and AHT prediction, which were mainly dependent on ALC (average local confidence; > 85%) and SVMS (vector machine software score, > 0) of the peptides calculated using the BIOPEP and AHTPDB databases, respectively [31,37]. The potential ACE-inhibitory activity, antihypertensive activity and physicochemical properties of the 17 peptides are shown in Table 2.…”
Section: In Silico Screening and Chemical Synthesis Of Ace-inhibitorymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years, rapid development of science and technology on preparation, purification, identification, and bioactive property evaluation takes a more promising future to ACE‐inhibitory peptides. Antihypertensive peptides derived from foods can play more important role in nutraceutical, pharmaceutical, and functional food industries (Capriotti, Cavaliere, Piovesana, Samperi, Laganà, 2016; Montone et al., 2018a; 2018b; Piovesana et al., 2018). Structure–activity relationship studies demonstrated that ACE‐inhibition activity of peptides is mainly depended on the connection mode between C ‐terminal residues of the peptides and the ACE active sites (Ling, Sun, & Zhuang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Indeed the fruitful use of waste or by-products also from other foods has been recently reviewed 5 as they can often represent a prodigious source of bio-compounds such as bioactive peptides 6,7 or free-seleno amino acids. 8 OMW is typically characterized by an intensive violet-dark brown up to black color, strong recognizable olive oil smell and high degree of organic pollution, with COD 40-220 g/L and BOD 5 35-110 g/L, TOC 25-45 g/L, pH between 4 and 6 and high content of polyphenols (0.5-24 g/L). 9 The phenolic fraction of OMW is very different from that of olive fruit; while olives are very rich in secoiridoid glucosides, OMW shows a high concentration of secoiridoid derivatives and by-products.…”
Section: Introductionmentioning
confidence: 99%